A comparison of heart rate variability, n-3 PUFA status and lipid mediator profile in age- and BMI-matched middle-aged vegans and omnivores. Issue 5 (3rd April 2017) - Pinto, Ana M.; Sanders, Thomas A. B.; Kendall, Alexandra C.; Nicolaou, Anna; Gray, Robert; Al-Khatib, Haya; Hall, Wendy L.
Abstract: Low heart rate variability (HRV) predicts sudden cardiac death. Long-chain (LC) n -3 PUFA (C20–C22) status is positively associated with HRV. This cross-sectional study investigated whether vegans aged 40–70 years ( n 23), whose diets are naturally free from EPA (20 : 5 n -3) and DHA (22 : 6 n -3), have lower HRV compared with omnivores ( n 24). Proportions of LC n -3 PUFA in erythrocyte membranes, plasma fatty acids and concentrations of plasma LC n -3 PUFA-derived lipid mediators were significantly lower in vegans. Day-time interbeat intervals (IBI), adjusted for physical activity, age, BMI and sex, were significantly shorter in vegans compared with omnivores (mean difference −67 ms; 95 % CI −130, −3·4, P <0·05), but there were no significant differences over 24 h or during sleep. Vegans had higher overall HRV, measured as 24 h standard deviation of normal-to-normal intervals (SDNN) (mean adjusted difference 27 ms; 95 % CI 1, 52, P =0·039). Conversely, vegans presented with decreased 8 h day-time HRV: mean adjusted difference in SDNN −20 ms; 95 % CI −37, −3, P =0·021, with no differences during nocturnal sleep. Day-time parameters of beat-to-beat HRV (root of the mean of the sum of the squares of differences between adjacent normal-to-normal intervals, percentage of adjacent normal-to-normal intervals that differ by >50 % and high-frequency power) were similarly lower in vegans, with no differences during sleep. In conclusion, vegans have higher 24 h SDNN, but lower day-time HRV and shorter day-time IBI relative to comparable omnivores. Vegans may have reduced availability of precursor markers for pro-resolving lipid mediators; it remains to be determined whether there is a direct link with impaired cardiac function in populations with low- n -3 status.